2011
DOI: 10.1177/0095244311414161
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the application properties of calcium sulfate whisker in silicone rubber composites

Abstract: Novel room-temperature-vulcanized silicone rubber/calcium sulfate whisker composites have been prepared. Properties such as viscosity, hardness, tensile strength, elongation at break, and thermal stability were researched and compared. A combination of scanning electronic microscopy studies was used to characterize the structure and reinforcing mechanism of calcium sulfate whisker. Results showed that the addition of 10% calcium sulfate whisker-Y into room-temperature-vulcanized composites improved the tensile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…Zhu et al studied the tribological properties of aramid fiber and CSW‐reinforced nonmetallic friction materials. Wang et al demonstrated that CSW improved tensile and thermal properties of silicone rubber. Li et al found that thermal stability of fluororubber (FPM)/CSW was better than that of FPM/anhydrous calcium sulfate composites.…”
Section: Introductionmentioning
confidence: 99%
“…Zhu et al studied the tribological properties of aramid fiber and CSW‐reinforced nonmetallic friction materials. Wang et al demonstrated that CSW improved tensile and thermal properties of silicone rubber. Li et al found that thermal stability of fluororubber (FPM)/CSW was better than that of FPM/anhydrous calcium sulfate composites.…”
Section: Introductionmentioning
confidence: 99%
“…The calcium sulfate whisker is a promising reinforcing material with a high aspect ratio [20]. Because of the remarkable advantages of high tensile strength and elastic modulus, calcium sulfate whiskers are often applied in rubber, paper, plastics, and ceramics as fillers to improve the comprehensive properties, including thermal stability, mechanical strength, chemical resistance, and electrical insulation [21][22][23][24]. The physical properties of the materials are highly dependent on the morphology of the whiskers [25].…”
Section: Introductionmentioning
confidence: 99%
“…Calcium sulfate whisker (CSW) is one of the representatives of such inorganic fillers that has many advantages such as high strength, low cost, non-toxicity, and environmentally-friendly nature, making it a desirable reinforcing agent in many fields such as papermaking [6] , plastics [7] , rubbers [8] , and adhesives. However, to the best of our knowledge, CSW has rarely been used to reinforce PVC.…”
Section: Introductionmentioning
confidence: 99%